Measurement of postmortem outflow facility using iPerfusion. (July 2022) - Madekurozwa, Michael; Reina-Torres, Ester; Overby, Darryl R.; van Batenburg-Sherwood, Joseph
Abstract: The key risk factor for glaucoma is elevation of intraocular pressure (IOP) and alleviating it is the only effective therapeutic approach to inhibit further vision loss. IOP is regulated by the flow of aqueous humour across resistive tissues, and a reduction in outflow facility, is responsible for the IOP elevation in glaucoma. Measurement of outflow facility is therefore important when investigating the pathophysiology of glaucoma and testing candidate treatments for lowering IOP. Due to similar anatomy and response to pharmacological treatments, mouse eyes are a common model of human aqueous humour dynamics. The ex vivo preparation, in which an enucleated mouse eye is mounted in a temperature controlled bath and cannulated, has been well characterised and is widely used. The postmortem in situ model, in which the eyes are perfused within the cadaver, has received relatively little attention. In this study, we investigate the postmortem in situ model using the iPerfusion system, with a particular focus on i) the presence or absence of pressure-independent flow, ii) the effect of evaporation on measured flow rates and iii) the magnitude and pressure dependence of outflow facility and how these properties are affected by postmortem changes. Measurements immediately after cannulation and following multi-pressure facility measurement demonstrated negligible pressure-independent flow in postmortem eyes, in contrast to assumptions made in previous studies. Using a humidity chamber, we investigated whether the humidity of the surrounding air would influence measured flow rates. We found that at room levels of humidity, evaporation of saline droplets on the eye resulted in artefactual flow rates with a magnitude comparable to outflow, which were eliminated by a high relative humidity (>85%) environment. Average postmortem outflow facility was ∼4 nl/min/mmHg, similar to values observed ex vivo, irrespective of whether a postmortem delay was introduced prior to cannulation. The intra-animal variability of measured outflow facility values was also reduced relative to previous ex vivo data. The pressure-dependence of outflow facility was reduced in the postmortem relative to ex vivo model, and practically eliminated when eyes were cannulated >40 min after euthanisation. Overall, our results indicate that the moderately increased technical complexity associated with postmortem perfusion provides reduced variability and reduced pressure-dependence in outflow facility, when experimental conditions are properly controlled. Highlights: Outflow facility in postmortem mouse eyes is similar to facility measured ex vivo . Postmortem pressure-independent outflow is indistinguishable from 0 nl/min. Inadequate hydration during perfusion can lead to substantial evaporative losses. Evaporative losses can induce an artefactual pressure-independent outflow. Humidity control with a hydrating fluid drop on the eye eliminates this artefact.